THE PECULIARITIES OF THE AMERICAN DREAM AND THE CHINESE DREAM CONCEPTS: COMPARATIVE STUDY - Simonov, Mykyta; Nelipa, Dmytro (Politology bulletin, 2023)
The article examines two concepts that are often used in the political environment of the United States of America and the People’s Republic of China. These are the American dream and the Chinese dream, which determine the domestic policy of the two centers of modern politics. The historical prerequisites of the American and the Chinese dream formation are analyzed and the most characteristic differences between the concepts of the Chinese and the American dream are identified. It is proved that, despite the closeness of the interpretation, the concept of the Chinese dream differs significantly from the American one in many respects. The differences in these concepts are due to historical factors, cultural development and geographical location, as well as China’s orientation to its own strength, in particular, the Chinese nation; the American dream is realized at the expense of the citizens of the United States, representing mostly different ethnic groups: they are given all the opportunities to realize their needs, including financial ones. As a result, Chinese dream rests on the power of the masses, the American dream on the nomination of an individual. t is determined that the ideas of the American and Chinese dreams play a significant role for both the American and the Chinese establishment. For the first, it is important to use the American dream and its realization as a tool of increasing the political support, while for the second, it is primarily the ideological unification of the Chinese nation.

У статті розглядаються дві концепції, часто використовувані у політичному середовищі Сполучених Штатів Америки та Китайської Народної Республіки: американська мрія та китайська мрія, що визначають внутрішню політику двох центрів сучасної політики. Проаналізовано історичні передумови їх формування та визначено найбільш характерні відмінності концепції китайської та американської мрії. Доведено, що, незважаючи на близькість тлумачення, концепція китайської мрії багато в чому істотно відрізняється від американської. Відмінності в цих поняттях зумовлені історичними факторами, культурним розвитком і географічним положенням, а також орієнтацією Китаю на власні сили та силу китайської нації; американська мрія реалізується за рахунок громадян Сполучених Штатів, що представляють переважно різні етнічні групи: їм надаються всі можливості для реалізації своїх потреб, у тому числі фінансових — як наслідок, китайська мрія тримається на владі мас, американська мрія — на номінації окремої людини. Обґрунтовано, що ідеї американської та китайської мрії відіграють важливу роль як для американського, так і для китайського істеблішменту. Для першого важливо активно використовувати американську мрію та її втілення як засіб посилення політичної підтримки, для другого ж — в першу чергу, ідеологічне об’єднання китайської нації.
ОСОБЛИВОСТІ КОНЦЕПЦІЙ АМЕРИКАНСЬКОЇ МРІЇ ТА КИТАЙСЬКОЇ МРІЇ: КОМПАРАТИВНЕ ДОСЛІДЖЕННЯ
Keywords: American dream; Chinese dream; domestic policy; strategic development; political concepts; американська мрія; китайська мрія; внутрішня політика; стратегічний розвиток; політичні концепції